Curaxin CBL0100 Blocks HIV-1 Replication and Reactivation through Inhibition of Viral Transcriptional Elongation - Jean, Maxime J.; Hayashi, Tsuyoshi; Huang, Huachao; Brennan, Justin; Simpson, Sydney; Purmal, Andrei; Gurova, Katerina; Keefer, Michael C.; Kobie, James J.; Santoso, Netty G.; Zhu, Jian (Frontiers in Microbiology, 2017)
Despite combination antiretroviral therapy (cART), acquired immunodeficiency syndrome (AIDS), predominantly caused by the human immunodeficiency virus type 1 (HIV-1), remains incurable. The barrier to a cure lies in the virus’ ability to establish a latent infection in HIV/AIDS patients. Unsurprisingly, efforts for a sterilizing cure have focused on the “shock and kill” strategy using latency-reversing agents (LRAs) to complement cART in order to eliminate these latent reservoirs. However, this method faces numerous challenges. Recently, the “block and lock” strategy has been proposed. It aims to reinforce a deep state of latency and prevent sporadic reactivation (“blip”) of HIV-1 using latency-promoting agents (LPAs) for a functional cure. Our studies of curaxin 100 (CBL0100), a small-molecule targeting the facilitates chromatin transcription (FACT) complex, show that it blocks both HIV-1 replication and reactivation in in vitro and ex vivo models of HIV-1. Mechanistic investigation elucidated that CBL0100 preferentially targets HIV-1 transcriptional elongation and decreases the occupancy of RNA Polymerase II (Pol II) and FACT at the HIV-1 promoter region. In conclusion, CBL0100 is a newly identified inhibitor of HIV-1 transcription that can be used as an LPA in the “block and lock” cure strategy.